KEY POINTS OF UNIVERSITY BUSINESS INCUBATORS : A SYSTEMATIC REVIEW AND FUTURE RESEARCH DIRECTIONS - Syahputra, Wira; Agustina, Tri Siwi (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2024)
The purpose of this study is to investigate the key components and best practices of University Business Incubators (UBIs), which are becoming increasingly important in encouraging innovation and economic growth by combining academic resources with entrepreneurial ventures. Despite its potential, little study has been conducted to establish a clear knowledge of the factors that influence UBI effectiveness. To fill this gap, a systematic review was performed with a focus on three research questions: (1) identifying theoretical frameworks that enable UBI development; (2) assessing empirical evidence on UBI operations. A comprehensive selection process began with 229 articles from Scopus and resulted in a final sample of 13 high-quality studies that were subjected to thematic synthesis analysis. The findings highlight key aspects such as technology adoption, coaching, human development, entry selection, and evaluation measures. Additionally, the results emphasize the importance of UBIs' external relationships, alignment with the Sustainable Development Goals (SDGs), and role in translating academic research into market-ready technologies via spin-offs. This analysis presents a complete framework for UBI optimization, providing actionable insights to increase their role in regional and national economic development while also filling important research gaps in UBI practices.